Collaborative Governance in Enhancing Public Transportation Quality: A Case Study of PT Dyda Silva Abadi Bus Trans NTT - Nadia Dwi Setyawati Adinda Rizky Sumbi; David B.W. Pandie; Aspri Budi Oktavianto (Jurnal Multidisiplin Sahombu, 2026)
East Nusa Tenggara (NTT), an archipelagic province comprising 1,192 islands with extreme geographical barriers, faces severe connectivity fragmentation that drives up logistics costs and limits public mobility. This study aims to analyze of the collaboration between the government and the private sector in improving the quality of public transportation services through the Trans NTT Bus innovation. This research employs a descriptive qualitative method with a phenomenological approach. Data were collected through observations, interviews, and documentation studies involving 28 informants. A purposive sampling technique was employed to select representatives from the NTT Provincial Transportation Office, PT Dyda Silva Abadi, PT ASDP Indonesia Ferry, and PT Dharma Lautan Utama (DLU) and accidental sampling was used to involve 20 passengers as respondents in the study. Data were collected using Governance framework[1]. The results indicate that the collaboration has been effective, producing intermediate outcomes in the form of ‘small wins’ such as affordable services through a one-ticket system, physical and cargo security guarantees, comfortable fleets, and easy accessibility between terminals. The dimensions of 'commitment to the process' and 'shared understanding' serve as major strengths, where all actors share a common vision to overcome geographical barriers. The level of trust among actors is significant, recorded at a score of 8.5 out of 10 (performance-based trust), evidence by long-term contracts and routine evaluations. However, the 'face-to-face dialogue' dimension remains bilateral in the field and lacks a routine formal coordination forum involving all actorss collectively. This study highlights the importance of establishing a formal coordination forum to strengthen managerial synchronization and ensure the long-term sustainability of collaboration in the public transportation sector.